2017
DOI: 10.1007/s10916-017-0722-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bioimpedianciometer as Predictor of Mountain Marathon Performance

Abstract: This study aimed to examine the relation among body composition, training experience and race time during a mountain marathon. Body composition and training pre-race experience analyses were conducted previous to a mountain marathon in 52 male athletes. A significant correlation between race time and mountain marathon with chronological age, body fat mass, percentage of body fat (BF), level of abdominal obesity, sport experience and daily training volume was revealed. In addition, BF and athlete's chronologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…They were barefoot and without excess clothing. Four foot electrodes were used, two of which were oval-shaped and two heel-shaped, and prior to testing, both the skin and the electrodes were cleaned and dried, then participants were asked to grip the palm and thumb electrodes (two of each electrode per athlete) according to previous report [27]. Body height was measured using a commercial scale.…”
Section: Methodsmentioning
confidence: 99%
“…They were barefoot and without excess clothing. Four foot electrodes were used, two of which were oval-shaped and two heel-shaped, and prior to testing, both the skin and the electrodes were cleaned and dried, then participants were asked to grip the palm and thumb electrodes (two of each electrode per athlete) according to previous report [27]. Body height was measured using a commercial scale.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that low body fat percentage (BF) was a key success factor in ultra-endurance races (Barandun et al, 2012), fact related with the large metabolic requirement (Clemente- Suarez, 2015) that could compromise even protein status, increasing the protein catabolism and muscle breakdown (Jamart et al, 2012). In this line, other researchers highlighted the importance of other parameters for this eliciting sport events founding how training schedule (Clemente- Suarez and Nikolaidis, 2017), odontological and nutritional variables , as well as emotional and personality constructs (Lane and Wilson, 2011). Considering the popularity of this sport (Vitti et al, 2020), it would be of great interest to examine long-term adaptations of health-related physical fitness to regular training in recreational marathon runners.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the quantity, but also the distribution of fat has health implications, with central fat related to risk for diseases such as coronary heart disease and stroke, whereas peripheral fat has less metabolic risk [9]. In addition to health, the fat distribution might have implications for endurance performance, e.g., it was shown that slow mountain marathon race time was related with a high level of central adiposity [10]. With regards to the role of sex, male swimmers had a more central distribution of fat, whereas women had more fat in their lower limbs [11].…”
Section: Introductionmentioning
confidence: 99%